Kehandalan Software Berdasarkan Data Sekunder Menggunakan Distribusi Poisson dan Kualifikasi Cronbach’s Alpha - Bambang Pudjoatmodjo; Mokhamad Hendayun (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2016)
In the last 17 years, the usage of computer software, such as operating system software and application software, (after the appearance of Windows 95) have increased rapidly. This is shown by the increasing number of choices for user to use the software to facilitate their work, such as word processing software, digital image processing, and financial application. A software must have a good reliability. It means the software can work according to the needs of the user. In addition, the software can perform fast recovery when subjected to disruption caused by mistakes made by users of the application. Therefore, we need a method for determining the software reliability. The assessment is based on the observation of failures occur in a certain interval range. Based on the observation we will determine the specific characteristics of data that will be used to select the probability distribution to determine the value of reliability. The type of data is secondary data (discrete). This aims to conduct a preliminary assessment before they are applied in real cases. The determination of reliability is used to draw conclusions on observations. Cronbach's Alpha scale is used to see how well the conclusions are drawn.